Performance evaluation of wire mesh heat exchangers. (25th March 2020) - Sayed, M.A.; ELdein Hussin, A.M.T.A.; Mahmoud, N.A.; Aboelsoud, W.
Highlights: Nu of the wire mesh HX increases on average 2.3 times that of the bare module. Correlation is developed to express Nu, Re and the dimensionless spacing. The 3 mm spacing module gives the highest Nu at constant pumping power. Mesh HX shows promising thermal performance at low cost. Abstract: Liquid-to-air cross-flow heat exchangers have a low heat transfer coefficient on the gas side due to poor thermal characteristics of air. One of the promising solutions is to attach extended surfaces on the gas side, thus increase the surface area of heat to transfer by convection. In this study, the experiment was carried out to evaluate the thermal and hydraulic performance of four modules of cross flow heat exchangers. One is bare copper tubes and three wire mesh heat exchangers with different mesh spacing. Hot distilled water was pumped into copper tubes at a constant flow rate of 9 l/min and inlet temperature of 80 °C. The heat exchanger subjected to external cross airflow inside an air duct of 20 cm × 20 cm cross-sectional area with an average air velocity of 2.8 m/s up to 14.9 m/s. Results showed an enhancement of Nusselt number for all wire mesh modules that is an increase of the volumetric heat transfer coefficient of up to 113.9% among the three tested modules compared to the bare module. The significance of this study is to use reasonably-priced wire mesh and maintain enhancement in the rate of heat transfer.